Electricity Utility Reform in Mali : Lessons from Operations - Gbedey, Franklin; Toga, Monyl (World Bank, Washington, DC, 2020)
In conflict-ridden Mali, where 61 percent of the population still lack access to electricity, demand for electricity is outpacing supply, limiting the country’s prospects for industrial and economic development. At the request of the Malian government, the World Bank launched a comprehensive assistance strategy to identify the causes of the financial difficulties of the electricity utility; devise a corporate and financial restructuring program; and provide targeted technical and financial support to address priority concerns. The actions have already borne fruit, improving the financial situation of the national utility. If all the issues identified are properly addressed, the utility will be able to reduce its reliance on government subsidies.